ESTIMATION OF SHEARWAVE VELOCITY (VS) USING HORIZONTAL-TO-VERTICAL SPECTRAL RATIO IN CENTRAL SULAWESI - Ratna Dewi, Sari
Sulawesi is one of the areas that has an active geological and tectonic setting. The active tectonic plate order makes the Sulawesi region vulnerable to potential earthquake hazards. The earthquake on September 28, 2022 with magnitudo (Mw) 7.5 is evidence of a significant and destructive earthquake occurrence in Sulawesi. To reduce losses due to earthquakes, it is necessary to conduct research on the dynamic response of the soil. In this thesis, the Horizontal-to-Vertical Spectral Ratio (HVSR) method is used to process microtremor data. The output obtained is dynamic parameters of the soil in form of dominant frequency, amplification, and shear wave velocity associated with the characteristics of the subsurface layer. This study uses waveform data from 33 stations spread across Central Sulawesi. The results of data processing show that the dominant frequency value ranges from 0,55 to 18,42 Hz. The dominant frequency has a high value at stations located close to the bay or beach and has a relatively thin sediment thickness, while amplification value is between 1,19 – 6,0. The inversion of HVSR curve was performed using the Neighbourhood Algorithm (NA). The Vs value is range from 74,44 – 3045,77 m/s with a depth of 818,56 meters. Classification of soil type based on the average value of Vs30 obtained that the soil types are medium soil (SD) and solid soil or soft rock (SC).